2013
DOI: 10.1155/2013/178346
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Direct Effects of Human Adipose- and Bone-Marrow-Derived Stem Cells on Postischemic Cardiomyoblasts in anIn VitroSimulated Ischemia-Reperfusion Model

Abstract: Regenerative therapies hold a promising and exciting future for the cure of yet untreatable diseases, and mesenchymal stem cells are in the forefront of this approach. However, the relative efficacy and the mechanism of action of different types of mesenchymal stem cells are still incompletely understood. We aimed to evaluate the effects of human adipose- (hASC) and bone-marrow-derived stem cells (hBMSCs) and adipose-derived stem cell conditioned media (ACM) on the viability of cardiomyoblasts in an in vitro i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Previous studies have revealed important differences between Ad-MSC and BM-MSC with respect to a variety of different properties, including osteogenesis, protection from sepsis, and healing of cardiac infarction [69][70][71][72]. Recently, the immune modulatory properties of human Ad-MSC and BM-MSC were compared [73].…”
Section: Immune Mechanisms Canine Mesenchymal Stem Cells 383mentioning
confidence: 99%
“…Previous studies have revealed important differences between Ad-MSC and BM-MSC with respect to a variety of different properties, including osteogenesis, protection from sepsis, and healing of cardiac infarction [69][70][71][72]. Recently, the immune modulatory properties of human Ad-MSC and BM-MSC were compared [73].…”
Section: Immune Mechanisms Canine Mesenchymal Stem Cells 383mentioning
confidence: 99%
“…De Coppi et al evaluated in vivo myogenesis following bladder injury and found that both BM-and AF-MSCs engaged significantly in preventing cryo-injury induced hypertrophy of surviving muscle cells [69]. This was supported by data showing that AT-MSCs and BM-MSCs protected cardiomyoblasts from cell death induced by ischemia-reperfusion to a similar degree in vitro [70]. Additionally, MSCs from cardiac tissues were proven to show higher cardiomyogenic differentiation in vivo than BM-MSCs following injection to infarcted left ventricle [25].…”
Section: Cell Therapymentioning
confidence: 94%